ETOS KERJA MASYARAKAT MISKIN PEDESAAN (STUDI FENOMENOLOGI PADA MASYARAKAT DESA SEWUREJO KECAMATAN MOJOGEDANG KABUPATEN KARANGANYAR) - Muchlisa Salma Nur Hartati; Drajat Tri Kartono (Universitas Sebelas Maret (UNS), 2019)
This research examines the poor residences living in Sewurejo Village that are included in IDT (Inpres Desa Tertinggal). The work ethic is one important factor for the framework of poor residences in Sewurejo Village. In fulfilling their daily needs, those residences need to work. The working habit of Sewurejo Village poor residents illustrates their work ethic in general. It can be used as a work ethic parameter of the poor residences and how the religion affects it. This research aims to determine the work ethic of poor residence and the effect of religion to work ethic. This research uses qualitative-phenomenological method and Protestant’s Ethic theory and Max Webber’s Capitalism Spirit. The samples are taken using purposive sampling.The results shows that Sewurejo Village residents are industrious and most of them work as construction workers, farm workers, merchants, industrial workers, and scavengers. For most of the residents of Sewurejo Village, the religion can affect the work ethic and vice versa, vice versa can also affect the work ethic. It can be seen in some indicators such as capital accumulation, religious manifestations, networks, and using their free time to worship so that they can go to heaven smoothly.